Exploring Undergraduate Pharmacy Students Perspectives Towards Antibiotics Use, Antibiotic Resistance, and Antibiotic Stewardship Programs Along With the Pharmacy Teachers’ Perspectives: A Mixed-Methods Study From Pakistan - Khan, Faiz Ullah; Khan, Amjad; Shah, Shahid; Hayat, Khezar; Usman, Abubakar; Khan, Farman Ullah; Khan, Zakir; Karataş, Yusuf; Ahmad, Tawseef; Chang, Jie; Malik, Usman Rashid; Khan, Asad; et al. (Frontiers in Pharmacology, 2021)
Background: Antibiotic resistance (ABR) is one of the major issues around the globe. Timely education and awareness of pharmacy students regarding the appropriate use of antibiotics, ABR, and antimicrobial stewardships are required. Methods: The present study was first conducted in 12 (public and private sector) universities among UGPS (n=414) irrespective of their study year through validated questionnaire from August 2019 to February 2020, and insight of pharmacy teachers was taken through in-depth semi-structured interviews in the second phase. For the quantitative data, different statistical methods were used and data were presented in tabulated form, whereas inductive thematic interpretation was used to categorize themes and derive conclusions from qualitative evidence. Results: The majority of the students were males (n=223, 54%) with the age group (mean: 19-23 years). Students have good knowledge about antibiotics use and the majority were purchased antibiotics through prescription (n=277, 54.8%) during the last month and strongly agreed to stop household storage of unnecessary (n=183 44.2). Most of the students have heard the terminologies related to antimicrobial resistance through social media while, unaware (n=104, 25.1%) of a Pakistan national action plan against AMR (antimicrobial resistance). Overall, respondents have a somehow good understanding of the ABR. Regular use of antibiotics without consultation of a physician can lead to ABR; were answered wrongly (162, 39.1%; p >0.05). The majority of the students (n=198, 47.8%) and teachers believe that the current pharmacy syllabus must be updated timely with the new subjects related to ABR and AMS in Pakistan. The UGPS have emphasized (n=220, 53.1%; Median=1, IQR=2) on establishing a link between academia and hospitals. Conclusion: Different training programs and events related to ABR and AMS are much needed in Pakistan. ABR and AMS-related course contents must be included in the current pharmacy curriculum of Pakistan.